Efek Pestisida Sevin 85 SP Terhadap Hama Kumbang Tanduk ( Oryctes rhinoceros ) Di Pembibitan Main Nursery Kelapa Sawit ( Elaeis guineensis Jacq) - Dungo Silaban; Novilda Elizabeth Mustamu; Siti Hartati Yusida Saragih (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2020)
Oil Paim seeding one  of the first oil Paim treatments in pre nursery and  main nursery  Sevin  85  SP pesticides reduce  pest  infestation on planst, sevin pesticides which can control  various pest attack beetles orytes rhinoceros horn beetles Orytes rhinoceros  horn  beetles in paim nurseries peramater observations include the  length of the hole hole, the  number of pests on plants , sevin pesticides which can control various attacks of beetle horn horns  Orytes  rhinoceros in nurseries oil paim peramater  the test  leaves consisted of 3 treatments of control S1 2 gr / 100 ml S2  3 gr / 200 ml from the resuts of the  S3 study with fewr ham attacks.Key words  :  Pesticida Sevin 85 SP,  Hornn  beet, effects of pesticides, oil paim seeds